THE DEPRESSION OF THE FEMALE CHARACTER IN THE MOVIE “FATHERS AND DAUGHTERS” 2015 - Nurdianty, Nurdianty; Sunra, La (Journal of English Literature and Linguistic Studies, 2024)
This research reveals the depression experienced by the female character in the movie "Fathers and Daughters", named Katie or Kate Davis. The aims of this study are to discover the type of depression and the causes of depression experienced by Katie, and to show the way to resolve her depression. Katie has been experiencing symptoms of depression since the age of 5 years since the car accident that caused her mother's death and then her father who died from mental illness psychosis he suffered from the accident. Until the age of 30 years she met Cameron, and then a romantic relationship that experienced many problems, separated and then back together again, which led to the peak of depression experienced by Katie. This research uses a pure structuralism approach and descriptive method in qualitative research to describe and analyze the data from the scenes and script of the movie. Thematic analysis is a method for identifying, analyzing, and reporting patterns (themes) within data. There are four results of this research. The first is that the researcher found the intrinsic element of the movie "Fathers and Daughters". The second result is the type of depression that Katie experienced: bipolar disorder. Bipolar disorder is a mood disorder characterized by periods of abnormally elevated mood known as mania. Bipolar disorder symptoms include fatigue, insomnia, lethargic, hopelessness, loss of self-esteem, irritability, and anxiety. The bitter incident, age factor, and substance abuse are the third result of the female character's depression. The last result is the way the female character resolves her depression.